Promoting sustainability in European language teaching - Maijala, Minna; Kuusalu, Salla-Riikka (Walter de Gruyter GmbH, 2026)
Sustainability has become a topical issue in many disciplines and increasingly also concerns language education and research, but the role of sustainability remains understudied in the field of language teaching. Consequently, language education could concentrate more on education for sustainable development (ESD) as it is considered crucial in reaching the sustainable development goals of Agenda 2030. Language education has immense potential to promote ESD because it deals with a wide range of cultural and societal themes and uses interactive teaching methods that contribute to democratic goals. Various language teaching methods are related to the components of the action-oriented ESD framework. Therefore, there are several features in language teaching that are already consistent with the principles of ESD. The Special Issue “Global goals for sustainability in European language teaching” aims to widen the perspectives around ESD in relation to language teaching, about its practical implementations in different countries and educational systems and open a discussion concerning what aspects in European and global language teaching could be promoted and further developed to support both the global sustainability goals and the future demands of language education. In this introduction, we discuss the principles of sustainability and ESD and the necessity of their implementation in foreign language education and elaborate on the gaps in understanding and implementation of sustainability in language teaching. Finally, we summarise the main points in each article of this Special Issue.